Recruiting clinical personnel as research participants: a framework for assessing feasibility - Hysong, Sylvia J (BioMed Central, 2013)
Increasing numbers of research studies test interventions for clinicians in addition to or instead of interventions for patients. Although previous studies have enumerated barriers to patient enrolment in clinical trials, corresponding barriers have not been identified for enrolling clinicians as subjects. We propose a framework of metrics for evidence-based estimation of time and resources required for recruiting clinicians as research participants, and present an example from a federally funded study. Our framework proposes metrics for tracking five steps in the recruitment process: gaining entry into facilities, obtaining accurate eligibility and contact information, reaching busy clinicians, assessing willingness to participate, and scheduling participants for data collection. We analyzed recruitment records from a qualitative study exploring performance feedback at US Department of Veterans Affairs Medical Centers (VAMCs); five recruiters sought to reach two clinicians at 16 facilities for a one-hour interview. Objective metrics were calculable for all five steps; metric values varied considerably across facilities. Obtaining accurate contact information slowed down recruiting the most. We conclude that successfully recruiting even small numbers of employees requires considerable resourcefulness and more calendar time than anticipated. Our proposed framework provides an empirical basis for estimating research-recruitment timelines, planning subject-recruitment strategies, and assessing the research accessibility of clinical sites.